“Zpěváček” Folk Singing Competition: Regional Identity and Heritage Performance in the Czech Republic - Skořepová, Zita (Traditiones, 2023)
“Zpěváček” is a competition for children singers of folk songs, which has been held in the Czech Republic since 1978 in several rounds, from regional to national. The article explores the ways in which the children act as performers of the (micro)regional identity and negotiate local cultural heritage. Accounting for both historical and contemporary contexts, the text draws from fieldwork including participant observation and autoethnography, interviews, and document analysis.